2009
DOI: 10.1159/000186694
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing in the Functional and Prognostic Evaluation of Patients with Pulmonary Diseases

Abstract: Exercise testing is increasingly utilized to evaluate the level of exercise intolerance in patients with lung and heart diseases. Cardiopulmonary exercise testing (CPET) is considered the gold standard to study a patient’s level of exercise limitation and its causes. The 2 CPET protocols most frequently used in the clinical setting are the maximal incremental and the constant work rate tests. The aim of this review is to focus on the main respiratory diseases for which exercise tolerance is indicated; for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 203 publications
(156 reference statements)
3
166
0
6
Order By: Relevance
“…Fell et al 19 also retrospectively showed a threshold of 8.3 mL/kg/min in peak V O 2 to predict survival of 117 IPF subjects, 19 whereas Triantafillidou et al 15 prospectively demonstrated a threshold of 14.2 mL/kg/min for survival among 25 subjects with IPF. 15 Despite the fact that peak V O 2 has been shown as an accurate and reliable prognostic predictor in many cardiopulmonary diseases, [8][9][10] in Fell's study, 19 only 8 subjects (6.83%) were below the 8.3 mL/kg/min threshold, but about 46% died, which make this threshold much less sensitive. 19 Furthermore, a threshold of 14.2 mL/kg/min seems to have a good sensitivity in predicting mortality based on the report of Triantafillidou et al 15 However, their findings are limited by a small sample size and so cannot be generalized, as well as contradicting previous reports.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Fell et al 19 also retrospectively showed a threshold of 8.3 mL/kg/min in peak V O 2 to predict survival of 117 IPF subjects, 19 whereas Triantafillidou et al 15 prospectively demonstrated a threshold of 14.2 mL/kg/min for survival among 25 subjects with IPF. 15 Despite the fact that peak V O 2 has been shown as an accurate and reliable prognostic predictor in many cardiopulmonary diseases, [8][9][10] in Fell's study, 19 only 8 subjects (6.83%) were below the 8.3 mL/kg/min threshold, but about 46% died, which make this threshold much less sensitive. 19 Furthermore, a threshold of 14.2 mL/kg/min seems to have a good sensitivity in predicting mortality based on the report of Triantafillidou et al 15 However, their findings are limited by a small sample size and so cannot be generalized, as well as contradicting previous reports.…”
Section: Discussionmentioning
confidence: 98%
“…8,9,12,33 Subjects were instructed to take their usual medications as prescribed. All tests were conducted between 8:30 a.m. and 12:30 p.m. to maximal subjective exertion level and respiratory exchange ratio (Ն1.1) and were supervised by a physician.…”
Section: Cpetmentioning
confidence: 99%
See 3 more Smart Citations